Clinical Pediatrics for Undergraduates - KE Elizabeth; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2009)
(3z(BClinical Pediatrics for Undergraduates(3y (BUG MBBS Syllabus of Medical Council of India (MCI), TUTORIAL and lecture topics, practical sessions the marks allotted, Pediatric case recording format, question model, marks and prescribed books are introduced in this book. Format for history taking and physical examination in pediatrics are elaborated. Normal growth and development and disorders related to growth and development in children are detailed. Definitions related to Neonatology, care of normal babies, Low birth weight (LBW) babies, and sick newborns, assessment of gestational age and neonatal resuscitation programme (NRP) and Neonatal advanced life support (NALS) are summarized. Details regarding various childhood vaccines, immunization schedules, immunization in immunosuppressed individuals, immunization in special situations, immunization among adolescents, and adverse effects of vaccines and maintenance of cold chain, vaccine vial monitor are included. Topics related to community pediatrics, various National programmes and Health indicators in vital statistics are included. Definitions related to nutrition, anthropometric measurements, interpretation, clinical features and spectrum of malnutrition, diagnosis and management of severe acute malnutrition (SAM), case studies leading to diagnosis and management of failure to thrive (FTT), edematous (Kwashiorkor) and non edematous (Marasmus) SAM are presented. An account of exanthematous fevers with related definitions, clinical course and complications are presented. Case studies based on Pyrexia of unknown origin (PUO) without any focus, and with hepatosplenomegaly, fever with malnutrition, immunosuppression, and persistent diarrhea suggestive of HIV-AIDS, tuberculosis, congenital imunodeficienct states, fever with polyarthritis are explained. A description of Kawasaki disease and collagen vascular diseases is also included. Various clinical features related to cyanotic and acyanotic congenital heart disease and acquired valvular heart disease are presented in a tabular format. A figure showing the various landmarks like mid sternal, mid clavicular and anterior, mid and posterior axillary lines is presented. Case studies related to left to right shunt, congestive heart failure, hypercyanotic blue spell, rheumatic Carditis and heart disease and infective encocarditis are included. Pictorial representation of the lobes and broncho-pulmonary segments, examples of clinical conditions with respect to site of involvement, and diagnosis of Acute Respiratory infection (ARI), danger signs in ARI are presented. Case studies illustrating Staphylococcal pneumonia with empyema, unresolved pneumonia, chronic lung infection and asthma diagnosis and management are included. A brief account of diarrheal diseases, watery diarrhea, osmotic and secretory, invasive diarrhea, ADD, persistent diarrhea, chronic diarrhea, diagnosis of dehydration, ORT, diarrhea control programme, approach to persistent diarrhea, dietary management are presented. Case studies of acute hepatitis, hepatic encephalopathy, persistent and chronic liver disease, hematemesis, a figure showing the various clinical quadrants of the abdomen and a table showing high gradient and low gradient ascites are included. A diagram showing the nephron and collecting tubule with an overview of the function of each area, Definitions related to Genitourinary system like oliguria, anuria, insensible loss of water, nephritic syndrome: frequent/infrequent relapse, steroid dependent/steroid resistant, minimal change/other types, differential diagnosis of hematuria in children, case studies related to nephritis and nephritic syndrome, comparative table showing features of nephritis and nephritic syndrome, urolithiasis and urinary tract infections are included. This book deals with normal hemoglobin in various age groups, WHO classification of anemia, case studies related to nutritional anemia, Hemolytic anemia, thrombocytopenia, hemophilia and leukemia and tables showing different acuses of anemia, differential diagnosis of hemolytic anemia, causes of thrombocytopenia, different coagulation defects, approach to bleeding diathesis, classification and treatment of leukemia. This book deals with common endocrine disorders like hypo and hyperthyroidism in children, endemic iodine deficiency, myxedematous and neurologic hypothyroidism, case study of Down syndrome, discussion on various autosomal and sex chromosome related conditions, microdeletions, prenatal diagnosis, triple and quadruple tests, table showing various major and minor congenital anomalies, and pedigree symbols. This book deals with CNS localization, UMN and LMN paralysis, Bladder innervations, CNS infections from newborn to childhood, brain abscess, TB meningitis, encephalitis, Differential diagnosis of small head primary and secondary microcephaly, differential diagnosis of large head-macrocephaly, megalencephaly, hydrocephaly, various types of cerebral palsy, mental retardation and rehabilitation, AFP differential diagnosis, AFP surveillance, Polio eradication programme and a schematic representation all the 12 cranial nerves and their location and function. This book deals with various pediatric emergencies, Quick ABC assessment, Holliday and Segar formula for maintenance fluid, calculation of surface area, interpretation of ABG, Cardio pulmonary resuscitation-BLS and ALS Algorithm, Tahycardia, bradycardia and Pulseless Algorithm, Acute adrenal insufficiency, Acute asthma, Acute renal failure, Approach to comatose child, AVPU Scale, Cyanotic spell, Dengue fever diagnosis and management, Drowning, foreign body aspiration, Hemlich$1 (Bs maneuver, hematemesis, hyperkalemia, hyponatremia, hypernatremia, Hypertensive emergencies, shock, status epilepticus, stridor, poisoning in children: general principles, hydrocarbon, organophosphorus, envenomation and so on. In this book includes the various equipments and instruments used in Pediatrics for diagnosis and therapy along with its uses and indications and interpretations. This book includes the probable stations and approach to practical examination in the field of objective structured clinical examination (OSCE), viva stations, pattern and approach and various illustrations of X-rays both common and uncommon. This book deals with drugs and dosages of antibiotics and all other medicines used in Pediatrics listed in an alphabetical order with dose, preparations and side effects. Three in One Weight, Height and BMI Charts (The ELIZ Health paths). WHO Growth charts, weight, height, weight for height, BMI charts. Fluid therapy- Preparations and Tips. Glasgow Coma scale for children and infants. Millennium Development goals and current status. Trivandrum developmental Screening chart (TDSC).s
Keywords: Pediatrics; Electronic books